Soil seedbanks in slash‐and‐burn rice fields of northern Laos. (17th October 2013) - de, A; Casagrande, M; Phaynaxay, K; Soulileuth, B; Saito, K; Johnson, David
Summary Crops in shifting cultivation fields often suffer from severe weed infestation when long fallow periods are replaced by short fallow periods. The soil seedbank as a source of weed infestation was studied in four fields that differed in their last fallow duration. The effect of burning was analysed by comparing adjacent pre‐burn and post‐burn samples (two sites). Surface vegetation was monitored from burning to harvest in the plots from which soil samples were taken to determine the fraction of the seedbank germinating (three sites). Seedbank size (1700–4000 seedlings m−2) varied depending on a single species, Mimosa diplotricha. Burning reduced emergence of most species, but stimulated emergence in others. Densities in the seedbank were not correlated with above‐ground abundances in the field, except for some species. Most species emerging after 50 days from the soil samples (40% of seedlings) were absent from the field after 190 days. Whilst the data from this study are derived from only four fields, the weed problems after short‐term fallowing appeared to be due to a larger fraction of the seedbank emerging, possibly due to shallow burial, and to a floristic shift towards adaption to burning, rather than the size of the seedbank per se.